Estimating of Some Interleukin Levels in Children with Amoebic Dysentery - Abdullah, Salam Khalid Mutlag (American Journal of Biomedicine and Pharmacy, 2025)
Gastrointestinal protozoan parasites are one of the major and pervasive health issues that affect more than three billion people globally. G. lamblia and E. histolytica were the most common intestinal parasites found in children and newborns, who make up the bulk of patients exposed to illnesses. Therefore, the purpose of this study was to estimate certain interleukin levels in children who had amoebic dysentery. To find out if the child had an E. histolytica infection, a general stool investigation was performed. A total of 120 youngsters under the age of 15 attended the parasitology unit between April and June of 2024. The chosen children experienced stomach ache and diarrhea. The results showed that 39(32.5%) samples were found positive for E. histolytica. The gender of patients showed significant (P≤0.05) differences. The percentage of infected male patients at (29.1%%) while, the percentage of female patients at (70.9%%). The results found that the concentration of IgM (187.01±17.75) and lgG (1532.5±45.61) showed significant (P≤0.05) elevated between E. histolytica patients compared to the control group (57.59±8.14; 729.4±16.22 respectively). The results found that the concentration of IL-6 (6.04±1.42) and IL-17 (18.74 ±1.03) show significant (P≤0.05) elevated between E. histolytica patients compared to the control group (2.63±0.45; 7.12±0.29 respectively). According to the current investigation’s findings, females have a greater infection rate than males. However, this study found that children with E. histolytica who had healthy observation collection had considerably greater serum levels of IL-6 and IL-17.